Cognition and Gait Show a Selective Pattern of Association Dominated by Phenotype in Incident Parkinson’s Disease - Lord, Sue; Galna, Brook; Coleman, Shirley; Yarnall, Alison; Burn, David; Rochester, Lynn (Frontiers in Aging Neuroscience, 2014)
Reports outlining the association between gait and cognition in Parkinson’s disease (PD) are limited because of methodological issues and a bias towards studying advanced disease. This study examines the association between gait and cognition in 121 early PD who were characterized according to motor phenotype, and 184 healthy older adults. Quantitative gait was captured using a 7m GAITrite walkway whilst walking for two minutes under single task conditions and described by five domains (pace, rhythm, variability, asymmetry and postural control). Cognitive outcomes were summarized by six domains (attention, working memory, visual memory, executive function, visuospatial function and global cognition). Partial correlations and multivariate linear regression were used to determine independent associations for all participants and for PD tremor-dominant (TD) and postural instability and gait disorder (PIGD) phenotypes, controlling for age, sex, and premorbid intelligence using the National Adult Reading Test (NART). Cognitive and gait outcomes were significantly worse for PD. Gait, but not cognitive outcomes, were selectively worse for the PIGD phenotype. Significant associations emerged for two gait domains for controls (pace and postural control) and four gait domains for PD (pace, rhythm, variability, and postural control).The strongest correlation was for pace and attention for PD and controls. Associations were not significant for participants with the TD phenotype. In early PD the cognitive correlates of gait are predominantly with fronto-executive functions, and are determined by the PIGD PD phenotype. These associations provide a basis for understanding the complex role of cognition in Parkinsonian gait.